STRATEGI KOMUNIKASI CLUB MOTOR INCLUDE PEKANBARU DALAM PEMBENTUKAN CITRA POSITIF - Beri, Okta; Sari, Genny Gustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Club motors are different from those of bende motorcycle that currently troubling the community. The community considers the club motor and bende motor is the same. In this case researchers want to explain that the motor club is different, if it is more deeply reviewed there is a negative view of the community, they consider the existence of the club motor unsettling. Club motors are more likely to be the directional activities of the Organization and have the rules in the club. Club Motors are more of a way on sports and their craze towards motors. Easy to characterize the motor club, one of which is not distracted in the street and orderly traffic. And bende motor tends to be free and undirected associations are not rules that bind someone in the assembly to obey them.This method of study is qualitative descriptive. Data analysis measures include observation, interviews, data collection, data reduction, data presentation, and withdrawal of conclusions. The subject involved in this study was determined based on the porposive technique that is the core manager of club motor include Pekanbaru. The purpose of this research is to know the strategy of Club motor include Pekanbaru in the formation of positive imagery.The results showed that club motor include Pekanbaru using communication strategy with the approach of strategic communication model is through the communicators strategy, where the Communicator Club motor include Pekanbaru in the delivery Information by conducting positive activities, such as conducting social service, not being distracted on the highway and appreciating highway riders in general. The target Audience club motor include Pekanbaru is the community around Basecamp and society generally. The media used is social media such as Facebook and Instagram. Keywords: positive image media strategi